THE IMPORTANCE OF MORPHOFUNCTIONAL INDICATORS IN THE DEVELOPMENT OF PHYSICAL QUALITIES IN YOUNG GRECO-ROMAN WRESTLERS: A REVIEW OF LITERATURE - Madaminov Khayrullo Akhmadjonovich (Innovate Conferences, 2025)
This article highlights the importance of morphofunctional indicators in the process of developing physical qualities in young Greco-Roman wrestlers, based on a review of literature. Research shows that morphological (height, weight, body proportions) and functional (cardiovascular, respiratory, and muscular activity) indicators play a crucial role in the selection of athletes and the optimization of their technical-tactical and physical preparation. The analysis of the literature demonstrates the necessity of scientifically grounded approaches in shaping physical qualities and organizing effective training for young athletes. Furthermore, the dynamics of morphofunctional indicators during different age periods have been examined, substantiating their direct impact on sports performance.
Keywords: Greco-Roman wrestling, young athletes, physical qualities, morphofunctional indicators, literature review, technical-tactical preparation, sports performance.